Vol tammetric determination of tin in juicy drink samples - Yahya, Mariana Yahya (Universiti Sains Malaysia, 2006)
A voltammetric method for analysis of tin in juicy drinks was developed using Anodic Stripping Voltammetry. A few parameters such as pH of the supporting electrolyte, initial potential, final potential, accumulation potential, accumulation time and scan rate were optimized. The optimum condition for the determination of tin in juicy drinks are, pH of BRB buffer is 2.32, initial potential is -0.6 V, final potential is -0.25 V, accumulation potential is 0 V, accumulation time is 90 seconds and scan rate is 10 m V /s. Various brands of juicy drinks that are commercially available are analyzed for determination of stannous/tin (IT) using the developed technique. The voltammetric measurements were carried out using Voltammetry Analyzer with three electrodes. The electrodes are Hanging Mercury Drop Electrode (HMDE) as the working electrode, auxiliary (platinum wire) and reference electrode (Ag/ AgCl/KCl). The concentration of tin is determined on each sample and then the result is compared with the standard limit set by World Health Organization (WHO). The result shows that Sn (ll) is absent in all the samples except three samples (sample B, M & N) which are from the same manufacturer. Finally, it can be concluded that the proposed method can be used for the determination on stannous in juicy drink samples.